2021
DOI: 10.1259/dmfr.20200309
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of high-resolution ultrasound (US) for gingival soft tissue thickness mesurement in edentulous patients prior to implant placement

Abstract: Objectives: To evaluate and compare the accuracy of high-resolution ultrasound (US) with two different cone beam CT (CBCT) units and clinical assessment for measuring gingival soft tissue thickness in edentulous patients prior to implant placement. Methods and materials: The study consisted of 40 maxillary implant sites of 40 healthy patients (20 females, 20 males; mean age, 47.88 years). We prospectively evaluated labial/buccal gingival thickness in 40 implant regions (16 anterior and 24 posterior) by using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…Borges et al 23 also found substantial differences in soft‐tissue measurements using ultrasonic devices and transgingival probing. However, Sönmez et al 32 reported that the two methods had no distinction. All three studies showed a strong correlation between gingival measurements acquired by CBCT and transgingival probing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Borges et al 23 also found substantial differences in soft‐tissue measurements using ultrasonic devices and transgingival probing. However, Sönmez et al 32 reported that the two methods had no distinction. All three studies showed a strong correlation between gingival measurements acquired by CBCT and transgingival probing.…”
Section: Resultsmentioning
confidence: 99%
“…One study assessed the index test before the reference standard by the same examiner, possibly introducing index test bias 24 . Regarding the reference standard bias, only three studies presented clear reference standards to classify gingival phenotypes 22,24,32 . Finally, all the articles defined the flowchart and timeframe of their cross‐sectional studies and thus had a low risk of flow and timing bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations